Alberto Cavalcanti e César Guerra-Peixe: contribuições sonoras para o cinema brasileiro - Cecilia Nazare de Lima (2012)
The fast appearing of Alberto Cavalcanti in Brazil was received with conflicting opinions and several critics, but this presentantion has the aim of highlight the contribuhition that his experience with the sound cinema brought to Brazilians films. Cavalcanti studied about the role of sound in the construction of the cinematographic language even though the subject was not yet commented in Brazil. His ideas about the three topics that compound the cinematographic sound: the word, the music and the noise, among other things, were applied on the soundtrack of Terra é sempre terra (Vera-Cruz, 1951) and O Canto do Mar (Kino Filmes, 1952/53), both made by Cavalcanti and with Guerra-Peixe's original music. The results of both films are analyzed in this study, which main reason is to investigate the application of cineast's sound ideas, the music contribution and the few musical researches of Guerra-Peixe for these production's sountrack. Besides his movies, Cavalcanti's opinions published in articles, interviews and in the book Filme e Realidade were also analyzed, as well as the characteristics of Guerra- Peixe's music and the outcomes of his searchs about the popular and folkloric music of northeast Brazil. The results affirm, among other things, the originality of the Cavalcanti's sound propositions (mainly the expressive use of noises and the application of functional noises) and the musical abundance of Guerra-Peixe's music (which changes with the narrative and closely relates with the soundtrack's multiple other factors). The use of musical manifestations, typical form northeast Brazil, was also noticed in the movie O Canto do Mar, according to the composer'smusicological notes.